Wulf Sachs, race trouble, and the will to know - Durrheim, Kevin (PINS-Psychology in Society, 2024)
The subtitle indicates that Wulf Sachs’ Black Hamlet (1937) is an expose: “The Mind of an African Negro revealed by Psychoanalysis”. The book is a psychobiography of John Chavafambira, whom Sachs describes as a “witch-doctor” who travelled to South Africa from a “kraal in Southern Rhodesia”, eventually taking up residence in Johannesburg. Sachs seeks to show the universality of the human mind. Although context, culture and “civilization” shape the superficial content of beliefs, motivations and delusions, Sachs “discovered” that “the manifestations of insanity, in its form, content, origins, and causation, are identical in both natives and Europeans.” (p 11) In this essay, I will consider what Black Hamlet reveals about the mind of a progressive white man living in South Africa in the 1930s – and, by extension, today. There can be no doubt that his work and close association with black people, including his visits to the Swartyard – an inner city black slum – and various rural kraals, must have cast Sachs as an outsider to white society at the time. Sachs was a progressive and he has been described both as a white “liberal” and as a “socialist” (Bloom, 2004).